2021
DOI: 10.1002/adfm.202107246
|View full text |Cite
|
Sign up to set email alerts
|

Radial Pores in Nitrogen/Oxygen Dual‐Doped Carbon Nanospheres Anode Boost High‐Power and Ultrastable Potassium‐Ion Batteries

Abstract: Constructing electrode materials with fast ions and electrons transport channels is an effective solution to achieve high-power-density and longcycle potassium-ion batteries (PIBs). Herein, completely opening radial pores in N/O dual-doped carbon nanospheres (RPCNSs) are constructed as anode for high-power PIBs. The RPCNS with hierarchical structure (micro/ meso/macropores and radial channels) and N/O dual-doping permits speedy ions and electrons transportation within the carbon nanospheres anode, achieving a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 137 publications
(106 citation statements)
references
References 75 publications
3
86
0
Order By: Relevance
“…As seen in Fig. 2h, all OFGC-500/600/700 display a typical type II Remarkably, the specific surface area of OFGC increases with the rise of temperature, which is consistent with the previous literature reports [27]. High nitrogen absorption at low relative pressure indicates that OFGC has high mesopores.…”
Section: Morphology Control and Characterization Of Ofgcsupporting
confidence: 90%
See 2 more Smart Citations
“…As seen in Fig. 2h, all OFGC-500/600/700 display a typical type II Remarkably, the specific surface area of OFGC increases with the rise of temperature, which is consistent with the previous literature reports [27]. High nitrogen absorption at low relative pressure indicates that OFGC has high mesopores.…”
Section: Morphology Control and Characterization Of Ofgcsupporting
confidence: 90%
“…Notably, O-doping can improve the wettability of the electrolyte and introduces more active sites, leading to better reaction kinetics. This has been reported in the previous literature [27]. However, whether COOH and C = O functional groups can store K + has not been studied.…”
Section: Morphology Control and Characterization Of Ofgcmentioning
confidence: 78%
See 1 more Smart Citation
“…[8][9][10] Typical design strategies such as heteroatom dopants (e.g., N, O) and edge-defect engineering in the carbonaceous matrix have been adopted to alleviate these issues to some extent. [11][12][13] One remaining dilemma resides in that deficient heteroatom dopants induce slightly improved electronic configurations (thus performance), whereas excessive sp 3 -C defects result in discrete domains with poor electron transport. As the case stands, new PIB electrode materials and judicious design strategies are needed to achieve satisfying performance.Metal-organic framework (MOF), consisting of metal ions/clusters covalently bonded with organic linkers, provides a potential carbonaceous platform for potassium ion storage.…”
mentioning
confidence: 99%
“…To understand the exact mechanism, in situ Raman can be a good solution, while Raman can provide the exact information of carbon materials. 45,[284][285][286][287][288][289][290][291] For example, Yi et al 291 have confirmed by in situ Raman that their composite materials go through two different reaction mechanisms, in which the formation of K 2 Se in the first convention reaction process and K 3 Sb phase in the following alloying reaction stage during K + storage at the Sb 2 Se 3 @C microtubes. Further, Chen et al 284 have also investigated the reaction mechanism by in situ Raman, in which they observed that the Bi 2 S 3 transformed into metal bismuth and the formation of Raman peak for C S bonds at 748 cm À1 , indicating an enhanced disorder graphitization after the potassiation process.…”
Section: Carbon Host For Metal-free Anodementioning
confidence: 99%